MiR-135a-5p promotes the migration and invasion of trophoblast cells in preeclampsia by targeting β-TrCP - Wu, Dongcai; Shi, Li; Hong, Lan; Chen, Xiaoju; Cen, Hui (Placenta (Eastbourne), 2020)
MiR-135a-5p is an important regulator of cell migration and invasion in several diseases. However, the biological functions and mechanisms of miR-135a-5p in women with preeclampsia (PE) remain unclear. The levels of miR-135a-5p and beta-transducin repeat containing E3 ubiquitin protein ligase (β-TrCP) expression in samples of placenta tissue from PE patients and healthy control subjects were determined by quantitative real-time PCR. The effects of miR-135a-5p and β-TrCP on cell migration, invasion, and epithelial-mesenchymal transition (EMT) in two trophoblast cell lines (HTR-8/SVneo and TEV-1) were examined using wound healing, Transwell, and western blot assays, respectively. A luciferase reporter assay was performed to confirm the association between miR-135a-5p and β-TrCP, and an in vivo mouse model was established and used to analyze the effect of β-TrCP on PE clinical phenotypes. We found that miR-135a-5p expression was significantly decreased and negatively correlated with β-TrCP expression in the placental tissues of pregnant women with PE. Cellular function experiments showed that overexpression of miR-135a5p promoted the migration and invasion of trophoblast cells in vitro. Furthermore, β-TrCP was confirmed as a target gene of miR-135a-5p in trophoblast cells. Notably, overexpression of β-TrCP significantly reversed the effect of miR-135a-5p on migration and invasion of trophoblast cells. At the molecular level, decreases in E-cadherin levels and increases in N-cadherin, Vimentin, and β-catenin levels that were induced by miR-135a-5p overexpression were attenuated by β-TrCP overexpression. Our findings demonstrate that miR-135a-5p promotes the migration and invasion of trophoblast cells by targeting β-TrCP. •MiR-135a-5p promotes trophoblast cell migration, invasion and EMT in PE.•MiR-135a-5p activates WNT/β-catenin signaling pathway through directly targeting β-TrCP.•NRX-252262, augments the PE clinical phenotypes in mice model.